Respostas
respondido por:
1
cancela os "n" e soma o resto (método da adição)
ficará:
4m = 14
m = 14 ÷ 4
m = 3,5
pra saber o valor de n, é só substituir o m por 3,5
2m + n = 6
2 • 3,5 + n = 6
7 + n = 6
n = 6 - 7
n = -1
ficará:
4m = 14
m = 14 ÷ 4
m = 3,5
pra saber o valor de n, é só substituir o m por 3,5
2m + n = 6
2 • 3,5 + n = 6
7 + n = 6
n = 6 - 7
n = -1
respondido por:
1
2m+n=6
2m-n=8 (soma)
2m=6
2m=8
4m=14
m=3,5
2m+n=6
2*3,5+n=6
7+n=6
n=-1
2m-n=8 (soma)
2m=6
2m=8
4m=14
m=3,5
2m+n=6
2*3,5+n=6
7+n=6
n=-1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás